Catalytic (asymmetric) methylene transfer to aldehydes - CONNON, STEPHEN; KAVANAGH, SARAH (My University, 2010)
An investigation into the poor activity of sulfides as catalysts for sulfonium-ylide-mediated methylene transfer to aldehydes has indicated that ylide formation is the problematic catalytic cycle step. Alkylation with traditional electrophiles does not proceed with sufficient efficiency to allow the sulfide to be used catalytically. Methyl triflate rapidly alkylates cyclic thiolanes under mild conditions, allowing their use in efficient aldehyde epoxidation reactions (in conjunction with phosphazene bases) at loadings as low as 10 mol%.
PUBLISHED
Highlighted in Synfacts (2010, 349).
Keywords: sulfonium-ylide-mediated methylene transfer to aldehydes; Chemistry; Nanoscience & Materials